PELAKSANAAN PERMOHONAN DISPENSASI KAWIN BATAS USIA NIKAH PEREMPUAN (Studi Penelitian di Wilayah Hukum Pengadilan Agama Lubuk Pakam) - Sudrajat, Raihan; Sulaiman, Sulaiman; Ramziati, Ramziati (Fakultas Hukum Universitas Malikussaleh, 2025)
The revision of the minimum legal age for marriage for females from 16 to 19 years, as stipulated in Law Number 16 of 2019 amending Law Number 1 of 1974 on Marriage, has resulted in a considerable increase in marriage dispensation requests at the Lubuk Pakam Religious Court. This situation highlights a gap between the normative goals of the legislative amendment and its practical application in society, where early marriage continues to be prevalent. This study seeks to examine and assess the rise in marriage dispensation applications and the underlying factors contributing to this trend, particularly in relation to the legal age of marriage for women within the jurisdiction of the Lubuk Pakam Religious Court. Utilizing an empirical juridical approach, this research draws on primary data gathered through interviews with informants and respondents, alongside secondary data derived from literature review. The data are analyzed qualitatively and presented in a descriptive format. The findings reveal that the increased number of marriage dispensation applications signifies the limited effectiveness of the age revision in curbing child marriage. Key contributing factors include limited legal literacy, economic challenges, religious considerations, and premarital pregnancy. Accordingly, there is a need for comprehensive preventive strategies and legal educational efforts to achieve the intended objective of child protection. It is recommended that legal awareness programs be reinforced, institutional roles be optimized, and community empowerment initiatives be expanded to mitigate the prevalence of underage marriage dispensations.